Balancing oncological control and immune preservation in the immunotherapy era: revisiting lymph node dissection in non-small cell lung cancer - Jing, Tao; Yang, Jianbao; Wei, Xiaoping; Wang, Cheng; Li, Bin (Frontiers in Oncology, 2025)
Systematic lymph node dissection (SLND) has long been widely accepted and established as a standard surgical procedure for lung cancer. In recent years, with the increased detection rate of early-stage non-small cell lung cancer (NSCLC) and the advancement of minimally invasive surgery and enhanced recovery concepts, approaches to lymph node dissection have undergone a notable shift. Previous studies have indicated that extensive removal of non-metastatic lymph nodes may offer uncertain clinical benefits. As a result, alternative strategies such as lobe-specific lymph node dissection (L-SLND) and lymph node sampling have gained attention among thoracic surgeons. In recent years, neoadjuvant chemoimmunotherapy for NSCLC has achieved remarkable success, with tumor-draining lymph nodes (TdLNs) playing a pivotal role in the efficacy of immunotherapy. Lymph node preservation strategies may synergize with immunotherapy by maintaining systemic immune surveillance. Conversely, the removal of non-metastatic lymph nodes could disrupt systemic immunity and exert secondary effects on primary tumors or potential micrometastases. This review summarizes the evolution of lymph node dissection strategies in lung cancer surgery and, in the context of encouraging outcomes with immunotherapy, provides new perspectives on future directions for balancing oncological control with immune preservation.